Rapid karstification process with evaporite-driven sinkholes in Southern Kohat Basin, NW Pakistan - Said Mukhtar Ahmad; Teng Wang; Saad Khan; Muhammad Waqar Azeem; Lv Fu (npj Natural Hazards)
Abstract Sinkholes are small karstic features in soluble rocks that play an essential role in karstification and cause severe environmental hazards. The Karak region of the Himalaya foothills showcases one of the best exposures of karstification landforms, given their highly soluble nature and salt dissolution activities. The well-developed sinkholes are unique worldwide, yet have not been investigated. Here, we apply Interferometric Synthetic Aperture Radar (InSAR), resistivity profiles, and field observations to study the karstification process in this region. InSAR detects numerous localized subsiding zones reflecting rates up to 29 mm/year from 2014 to 2023. Resistivity profiles and field observations catalog them as cover collapse, bedrock collapse, and bedrock sagging sinkholes, carrying distinctive evaporite-driven dissolution features controlled by faulting activity. The results enhance our understanding of the linkages between sinkhole development, subsidence, and subsurface structures, emphasizing the need for comprehensive planning to mitigate future hazards in this less-representative yet populated region.